Researching the autism spectrum : - Roth, Llona (Jessica Kingsley, 2010)
"This selection of contemporary research provides up-to-date perspectives from leading investigators who are at the cutting edge of studies in autism spectrum disorders. The book allows readers to grasp new approaches to understanding the autism spectrum. Key areas of theory and research are covered, from classification and diagnosis, genetics, neurology and biochemistry, to socio-cognitive, developmental and educational perspectives, essential to a broader understanding of the autism spectrum. In addition it introduces new emphases on MEG, epilepsy and memory. In highlighting both biomedical and psychological perspectives, this book reflects the multi-level emphasis of contemporary thinking about autism. By addressing key unanswered questions, Researching the Autism Spectrum acts as a guidepost for future research and provides an authoritative and multidisciplinary perspective"--